Graphene-coated nanowires with drop-shaped cross section for the low loss propagation of THz waves with sub-micron mode widths. (13th July 2018) - Cong, Xuan; Huang, Yingxue; Zhang, Min; Su, Hong; Li, Irene Ling; Liang, Huawei
Abstract: Both the strong mode confinement and the low propagation loss are very important for the design of highly integrated THz devices, but they are often contradictory to each other and difficult to be achieved at the same time. In this paper, we study the inside-dominant graphene surface plasmon polaritons (GSPPs) propagating on the graphene-coated nanowires with drop-shaped cross section using COMSOL multiphysics. We find that the THz GSPPs achieve not only the sub-micron mode width but also the long propagation length. Furthermore, the inside-dominant GSPPs have very high energy utilization efficiency, because almost all the mode power is inside the nanowire. These excellent characteristics make the mode very useful in the nanophotonics, bio-photonics and highly integrated THz circuits.